The roots of mathematics teaching modernization in Portuguese liceus (1957-1967) - Almeida, Mária (2026)
The Modern Mathematics (MM) reform took place between the 1950s and 1970s across much of the world and was associated with a profound change in content, as well as an alteration in teaching methodologies and the language of school mathematics. This essay investigates the modernization of mathematics education in Portugal during the period 1957–1967, aiming to identify international influences on the intentions behind the renewal of mathematics teaching; to detect similarities in the context of the introduction of Modern Mathematics in Portugal, the United States, and Europe; and to determine the contribution of the OECD to the introduction of MM. The text begins with a contextualization of the origins of the Modern Mathematics reform in Europe and the United States, and of the Portuguese political-educational reality, including international intervention. We then discuss the origins of the modernization of mathematics teaching in Portugal, based on the following questions: What were the initial intentions and purposes? What was the contribution of the international context? What similarities can we find between the introduction of MM in Portugal and other countries? Our analysis revealed that there was an internal reflection of international movements and transformations regarding mathematics education. The intentions to renew mathematics teaching sought a closer alignment between secondary and higher education mathematics, anchored in the role that mathematics was called upon to play in science, technology, industry, among others. Portuguese reformers thus adopted the arguments used by American reformers to justify the need for a new mathematics. The knowledge circulating in Portugal about the new ideas was aligned with the modern vision of mathematics education promoted by the European reform movement. OECD’s support for the modernization of education was legitimized by its urgency, particularly regarding the updating of teachers in terms of content and pedagogical aspects. The text is based on a documentary analysis of a descriptive and interpretative nature, with a historical perspective. We have used documentation published in specialized journals, archival materials, participant testimonies, and articles published in the press.